M. J. Spalding correspondence - Spalding, M. J. (Martin John), 1810-1872.
Two ALS, one (1866 January 25) written from Washington, D.C., and the other (1867 Jan. 24) from Baltimore, Md., both of a social nature, addressed to a cousin.
Clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Baltimore (Md.) -- Social life and customs; Washington (D.C.) -- Social life and customs; Clergy